A survey of UK healthcare workers' attitudes on volunteering to help with the Ebola outbreak in West Africa. - Lance Turtle; Fiona McGill; Judy Bettridge; Claire Matata; Rob Christley; Tom Solomon (PLoS ONE)
Objective To understand the barriers and enablers for UK healthcare workers who are considering going to work in the current Ebola outbreak in West Africa, but have not yet volunteered. Design After focus group discussions, and a pilot questionnaire, an anonymous survey was conducted using SurveyMonkey to determine whether people had considered going to West Africa, what factors might make them more or less likely to volunteer, and whether any of these were modifiable factors. Participants The survey was publicised among doctors, nurses, laboratory staff and allied health professionals. 3109 people answered the survey, of whom 472 (15%) were considering going to work in the epidemic but had not yet volunteered. 1791 (57.6%) had not considered going, 704 (22.6%) had considered going but decided not to, 53 (1.7%) had volunteered to go and 14 (0.45%) had already been and worked in the epidemic. Results For those considering going to West Africa, the most important factor preventing them from volunteering was a lack of information to help them decide; fear of getting Ebola and partners' concerns came next. Uncertainty about their potential role, current work commitments and inability to get agreement from their employer were also important barriers, whereas clarity over training would be an important enabler. In contrast, for those who were not considering going, or who had decided against going, family considerations and partner concerns were the most important factors. Conclusions More UK healthcare workers would volunteer to help tackle Ebola in West Africa if there was better information available, including clarity about roles, cover arrangements, and training. This could be achieved with a well-publicised high quality portal of reliable information.